2022
DOI: 10.3390/molecules28010302
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biological Activities of Naturally Occurring and Structurally Modified Podophyllotoxins

Abstract: Plants containing podophyllotoxin and its analogues have been used as folk medicines for centuries. The characteristic chemical structures and strong biological activities of this class of compounds attracted attention worldwide. Currently, more than ninety natural podophyllotoxins were isolated, and structure modifications of these molecules were performed to afford a variety of derivatives, which offered optimized anti-tumor activity. This review summarized up to date reports on natural occurring podophyllot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 251 publications
0
11
0
Order By: Relevance
“…drugs due to their high cytotoxicity against various tumour cell lines. 16 Chromene derivative analogues of the podophyllotoxin lignan were first synthesised by Jurd (1997) 17 and later by Frackenpohl et al (2009) 18 using the procedure shown in Scheme 1. The derivatives were obtained in yields ranging from 5 to 35%.…”
Section: Letter Synlettmentioning
confidence: 99%
See 2 more Smart Citations
“…drugs due to their high cytotoxicity against various tumour cell lines. 16 Chromene derivative analogues of the podophyllotoxin lignan were first synthesised by Jurd (1997) 17 and later by Frackenpohl et al (2009) 18 using the procedure shown in Scheme 1. The derivatives were obtained in yields ranging from 5 to 35%.…”
Section: Letter Synlettmentioning
confidence: 99%
“…These compounds were tested against various cancer cell lines and showed significant cytotoxicity comparable to their natural analogue, podophyllotoxin. 14,16 However, the low yields and lengthy process required to obtain these compounds present obstacles to conducting further in-depth studies with the tumour cell lines in which they were found to be active. 14,17,18 Scheme 1 Synthetic route used by Jurd (1997) 17 and Frackenpohl et al (2009) 18 Given the importance of these derivatives in developing new anticancer drugs, this work describes obtaining derivative 5 for the first time from a multicomponent reaction between tetronic acid 1, aromatic aldehyde 2, and a phenol 3 in the presence of an acid promoter.…”
Section: Letter Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…12) and its analogues have been isolated in enantiopure form in not less than nine distinct and taxonomically unrelated plant families. 96…”
Section: The Origin Of Scalemic Natural Productsmentioning
confidence: 99%
“…12) and its analogues have been isolated in enantiopure form in not less than nine distinct and taxonomically unrelated plant families. 96 The different enantiopurity of lignin and lignans is related to the cellular milieu where the monoelectronic oxidation takes place. The dimerization of monolignol, as exemplied by coniferyl alcohol ( 60) is initiated by a single-electron transfer catalysed by a laccase or a peroxidase (Scheme 14).…”
Section: Reviewmentioning
confidence: 99%